2012
DOI: 10.1080/10962247.2012.686441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and mechanisms of hydrogen sulfide adsorption by camphor-derived biochar

Abstract: The characteristics and mechanisms of hydrogen sulfide (H2S) adsorption on a biochar through pyrolysis at various temperatures (100 to 500 degrees C) were investigated. The biochar used in the current study was derived from the camphor tree (Cinnamomum camphora). The samples were ground and sieved to produceparticle sizes of 0.4 mm to 1.25 mm, 0.3 mm to 0.4 mm, and <0.3 mm. The H2S breakthrough capacity was measured using a laboratory-designed test. The surface properties of the biochar were characterized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Selection of particle size of an adsorbent is significant to enhance the adsorption ability of the material [30,31]. Particles with larger diameter have lower adsorption ability of hydrogen sulfide from biogas than the particle of smaller size [32,33]. According to our study, outcomes on hydrogen sulfide adsorption using red rock samples of different particle size are obtained as shown in Figure 5.…”
Section: Adsorptionmentioning
confidence: 87%
“…Selection of particle size of an adsorbent is significant to enhance the adsorption ability of the material [30,31]. Particles with larger diameter have lower adsorption ability of hydrogen sulfide from biogas than the particle of smaller size [32,33]. According to our study, outcomes on hydrogen sulfide adsorption using red rock samples of different particle size are obtained as shown in Figure 5.…”
Section: Adsorptionmentioning
confidence: 87%
“…The green waste-derived biochar recorded the second highest breakthrough capacity (6.5 g S/kg medium). While this value was within the wide range measured by Shang et al (2012) (1.1-114 g S/kg medium) for camphor derived biochar, it was considerably lower than the capacities reported by Shang et al (2013) which ranged from 109 to 383 g S/kg medium for biochars derived from agricultural/forestry wastes products such as camphor, rice hulls and bamboo. Others have reported on engineered GAC which has been impregnated with caustic compounds (Siefers, 2010;Abatzoglou and Boivin, 2009) such as sodium hydroxide (NaOH) or potassium hydroxide (KOH), sodium bicarbonate (NaHCO 3 ) and sodium carbonate (Na 2 CO 3 ) or strong oxidising agents such as potassium permanganate (KMnO 4 ).…”
Section: 2mentioning
confidence: 61%
“…Biochar is known as black carbon that is formed by the pyrolysis of biomass and is referred to as a 'super sorbent' for contaminants (Shang et al, 2012). Many studies have shown that soil amendment with biochar could enhance soil adsorption of contaminants and thus reduce their bioavailability and leaching risk (Cabrera et al, 2011;Lü et al, 2012;Song et al, 2013).…”
Section: Introductionmentioning
confidence: 99%